Ansel Adams at 100. - Fiorina, Carly; Phillips, Sandra S.; Ross, David A.; Szarkowski, John; Exhibition. Ansel Adams at 100 (1). Exhibition. Ansel Adams at 100 (2). Exhibition. Ansel Adams at 100 (3). Exhibition. Ansel Adams at 100 (4). Exhibition. Ansel Adams at 100 (5). Exhibition. Ansel Adams at 100 (6). Art Institute of Chicago. Hayward Gallery London. Kunstbibliotek Berlin. LACMA (Los Angeles County Museum of Art) Los Angeles. MoMA (The Museum of Modern Art) New York. SFMOMA (San Francisco Museum of Modern Art) San Francisco. 2001-08-04. 2002-02-20. 2002-07-04. 2002-10-10. 2003-02-02. 2003-07-09. 2002-01-13. 2002-06-02. 2002-09-22. 2003-01-05. 2003-04-27. 2003-11-04 (San Francisco : SFMOMA (San Francisco Museum of Modern Art) San Francisco, 2001)
In commemoration of the one hundredth anniversary of the birth of Ansel Adams (1902-1984), the centennial exhibition Ansel Adams at 100 presents a surprising new look at this legendary photographer's work. Organized by the San Francisco Museum of Modern Art, the exhibition is directed by the distinguished curator John Szarkowski, director emeritus of the Department of Photography at New York's Museum of Modern Art. Szarkowski has painstakingly selected what he considers Adams' finest work and has attempted to find the single best photographic print of each. Szarkowski notes that Ansel Adams at 100 is the product of a thorough review of work that Adams, at various times in his career, considered important. It includes many photographs that will be unfamiliar to lovers of Adams' work, and a substantial number that will be new to Adams scholars. The book is an attempt to identify that work on which Adams' claim as an important modern artist must rest. Ansel Adams at 100 - the exhibition and the book, with Szarkowski's incisive critical essay - is the first serious effort since Adams' death in 1984 to reevoluate his achievement as an artist. This special museum edition also includes a foreword by Sandra S. Phillips that situates Adams' lifework within the context of his native San Francisco. The exhibition prints, drawn from important public and private collections, have been meticulously reproduced in tritone to create the splendid plates in this catalogue, faithfully rendering the nuances of the original prints.The images have been scaled to reflect the relative sizes of the original photographs and have been impeccably printed on specially made paper from France. The companion volume to an international traveling exhibition, Ansel Adams at 100 is destined to be the definitive book on this great American artist.
biog. auteurs achterflap
Engels
boek
Keywords: Adams, Ansel